Gender Equality in Shigematsu Kiyoshi's Novel Tsubame Kinenbi - Wiastiningsih (Japanology: The Journal of Japanese Studies, 2023)
Shigematsu Kiyoshi's novel "Tsubame Kinenbi," published on March 15, 2008, explores the life of a family navigating child-rearing and professional challenges in Japan. The narrative focuses on Yuki's mother, who faces significant hurdles reintegrating into the workforce after maternity and childcare leaves, spotlighting the societal and workplace obstacles that working mothers often encounter. This study analyzes how the novel constructs gender equality and portrays gender roles, using thematic analysis to delve into narrative structure and character development. The findings reveal that despite supportive policies like maternity and paternity leave, traditional gender roles and societal expectations persist. The novel also addresses community reactions to child-rearing activities and depicts a supportive marital dynamic where both partners actively participate in parenting and personal development, challenging conventional gender norms. "Tsubame Kinenbi" advocates for a shift towards shared parental responsibilities and better support systems, promoting a balanced approach to gender equality and emphasizing the ongoing complexities in achieving such equality in modern Japan.